2023
DOI: 10.1097/dad.0000000000002381
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin 1 and p53 Expression in Cutaneous Squamous Cell Carcinoma and Precursor Lesions

Abstract: Studies on the relationship between stathmin 1 (STMN1) and cutaneous squamous cell carcinoma (cSCC) are limited. We aimed to evaluate the relationship between clinicopathological factors and STMN1 and p53 expressions in cSCC and compare them with those in the precursor lesions of cSCC and normal tissue. A total of 195 patients, followed between January 2014 and December 2021, with diagnoses of primary cSCC (n = 129), in situ cSCC (n = 20), or actinic keratosis (n = 46), as well as 29 histopathologically normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Therefore, STMN1 phosphorylation indirectly promotes tubulin polymerization and stabilizes microtubules [ 13 ]. Studies have confirmed that STMN1 is highly expressed in cutaneous squamous cell carcinoma and is associated with lesion grade [ 14 ]. p53 is the most tumor-related gene, and its mutation is considered to be the main cause of malignant tumor occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, STMN1 phosphorylation indirectly promotes tubulin polymerization and stabilizes microtubules [ 13 ]. Studies have confirmed that STMN1 is highly expressed in cutaneous squamous cell carcinoma and is associated with lesion grade [ 14 ]. p53 is the most tumor-related gene, and its mutation is considered to be the main cause of malignant tumor occurrence and development.…”
Section: Discussionmentioning
confidence: 99%